Case report on antipsychotic induced catatonia in an incarcerated patient - Nguyen, Han; Cannell, Ruslana; Rollakanti, Suman; Rosenthal, Johanna; Seigler, David (Frontiers in Psychiatry, 2023)
Antipsychotic-induced catatonia is an iatrogenic and debilitating adverse reaction, but there is a dearth of recent documented cases. This report describes a 35-year-old incarcerated Korean-American male with a history of unspecified psychosis who presented for antipsychotic induced catatonia after administration of haloperidol decanoate intramuscular (200 mg across the span of 1 week). Neurologic workup was performed including MRI, lumbar puncture, and electroencephalography. Despite an approximate month long hospitalization, benzodiazepine challenge, benztropine trial, and amantadine adjunct, our patient continued to experience bradykinesia, waxy flexibility, and mask-like facies, and was minimally verbally responsive. Several challenges in the treatment of incarcerated individuals at the hospital are highlighted in this case report, including adverse reaction to medication, difficulty of care coordination, and limited access to health records among providers.